2023
DOI: 10.1021/acs.energyfuels.3c00545
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced ORR Activity of A-Site-Deficient SrCo0.8Nb0.1Ti0.1O3−δ as a Bifunctional Air Electrode for Low-Temperature Solid Oxide Fuel Cells

Abstract: Solid oxide fuel cells (SOFCs) working at intermediate and low temperatures (≤650 °C) demonstrate tremendous potential benefits including their ease of manipulation, improvement in durability, and utilization of metallic interconnects. However, the sluggish oxygen reduction reaction (ORR) of air electrodes at lower temperatures is the main reason for constraining their supply of power. In this work, an A-site-deficient perovskite Sr0.95Co0.8Nb0.1Ti0.1O3−δ (S0.95CNT) has been developed as a bifunctional air ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
(63 reference statements)
0
8
0
Order By: Relevance
“…The semiconducting behavior converts to the metal-conducting behavior after ∼500 °C. A similar trend of the conducting behavior can be seen in other perovskite-based cathodes . The transition of conductive behavior can be explained by the formation of additional oxygen vacancies after the inflection point temperature.…”
Section: Results and Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The semiconducting behavior converts to the metal-conducting behavior after ∼500 °C. A similar trend of the conducting behavior can be seen in other perovskite-based cathodes . The transition of conductive behavior can be explained by the formation of additional oxygen vacancies after the inflection point temperature.…”
Section: Results and Discussionmentioning
confidence: 86%
“…When the temperature is below 550 °C, the SCF exhibits a large ASR value, indicating that W doping can lead to ORR activity enhancement, especially at low temperatures. To provide evidence for the reliability of the experiment results, EIS values at 600 °C of all samples are fitted by an equivalent circuit model. ,, In this fitted model, R 1 is related to the resistance from the electrolyte, and R 2 and R 3 represent the resistance of different reaction processes, e.g., charge transfer from the electrolyte to the cathode and the oxygen surface (exchange and diffusion) process, respectively. In addition, CPE1 and CPE2 are constant phase elements.…”
Section: Results and Discussionmentioning
confidence: 99%
“…71 A 5% A-site deficient perovskite of Sr 0.95 Co 0.8 Nb 0.1 Ti 0.1 O 3− δ (S0.95CNT) could increase the concentration of oxygen vacancies. 72 At 600 °C, the S0.95CNT air electrode exhibited an 18% performance improvement over the deficiency-free SCNT counterpart. 72 Moreover, Shi et al demonstrated that the deficiency of 5% Ba in the BaCoO 3 air electrode could improve the protonation ability and reduce the energy barrier in the proton migration process according to first-principles calculations.…”
Section: Strategies For Electrochemical Performance Enhancementmentioning
confidence: 94%
“…72 At 600 °C, the S0.95CNT air electrode exhibited an 18% performance improvement over the deficiency-free SCNT counterpart. 72 Moreover, Shi et al demonstrated that the deficiency of 5% Ba in the BaCoO 3 air electrode could improve the protonation ability and reduce the energy barrier in the proton migration process according to first-principles calculations. 61 And the surface catalytic activity of O 2 and the chemical stability of the Ba 0.95 CoO 3 compound are also strengthened.…”
Section: Strategies For Electrochemical Performance Enhancementmentioning
confidence: 94%
See 1 more Smart Citation